2013
DOI: 10.1371/journal.pone.0067044
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Regional CBF by L-Serine Contributes to Its Neuroprotective Effect in Rats after Focal Cerebral Ischemia

Abstract: To investigate the mechanisms underlying the neuroprotective effect of L-serine, permanent focal cerebral ischemia was induced by occlusion of the middle cerebral artery while monitoring cerebral blood flow (CBF). Rats were divided into control and L-serine-treated groups after middle cerebral artery occlusion. The neurological deficit score and brain infarct volume were assessed. Nissl staining was used to quantify the cortical injury. L-serine and D-serine levels in the ischemic cortex were analyzed with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…These results are consistent with our previous observations on the therapeutic effect of L-serine in transient and permanent cerebral ischemic rats [21], [22]. The present study extended the observation time to 35 days after cerebral ischemia and more parameters, especially the learning and memory that were used to evaluate the recovery of neurological functions in rat.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with our previous observations on the therapeutic effect of L-serine in transient and permanent cerebral ischemic rats [21], [22]. The present study extended the observation time to 35 days after cerebral ischemia and more parameters, especially the learning and memory that were used to evaluate the recovery of neurological functions in rat.…”
Section: Discussionsupporting
confidence: 93%
“…These are novel mechanisms underlying the therapeutic effect of L-serine for the rats with ischemic brain injury, in addition to the glycine receptor-mediated neuroprotective mechanism and the endothelial apamin- and charybdotoxin-sensitive Ca 2+ -activated K + channels-mediated vasodilation mechanism we reported previously [21], [22]. Thereby, combining with present results we reported here, we suggest that L-serine might be a new candidate for the treatment of ischemic brain injury because of its actions on multiple targets.…”
Section: Discussionmentioning
confidence: 89%
“…L‐serine is a crucial neurotrophic factor in the CNS as it is a precursor for nucleotides, neurotransmitters, sphingolipids, phosphatidylserine, and L‐cysteine (Ren et al . ). Moreover, the increased levels of neuronal‐specific ENO2 and 3‐PGDH are likely a cellular stress response to prevent cell death in the absence of PINK1 (presence of mitochondrial dysfunction), consistent with the finding that blocking glycolysis in PINK1‐deficient mouse embryonic fibroblasts led to rapid death of these cells (Akundi et al .…”
Section: Discussionmentioning
confidence: 97%
“…To conclude, there are very few MoorVMS-OXY studies done on humans, but from the literature found, it is used widely showing it is reliable and clinically applicable [26][27][28][29][30][31][32]. Oxygen is vital to ensure wound healing, and a lack of oxygen can delay the healing process [2].…”
Section: Discussionmentioning
confidence: 99%